2019
DOI: 10.1126/science.aav4687
|View full text |Cite
|
Sign up to set email alerts
|

Keyhole threshold and morphology in laser melting revealed by ultrahigh-speed x-ray imaging

Abstract: We used ultrahigh-speed synchrotron x-ray imaging to quantify the phenomenon of vapor depressions (also known as keyholes) during laser melting of metals as practiced in additive manufacturing. Although expected from welding and inferred from postmortem cross sections of fusion zones, the direct visualization of the keyhole morphology and dynamics with high-energy x-rays shows that (i) keyholes are present across the range of power and scanning velocity used in laser powder bed fusion; (ii) there is a well-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
260
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 733 publications
(328 citation statements)
references
References 26 publications
21
260
2
2
Order By: Relevance
“…The experimental schematic is shown in Fig. S1 of the Supplemental Material [6], with the details in Appendix A [7,23,24]. Figure 1 and Supplemental Material Fig.…”
Section: A Mhz Synchrotron-x-ray Imaging Of Laser-induced Spatteringmentioning
confidence: 99%
“…The experimental schematic is shown in Fig. S1 of the Supplemental Material [6], with the details in Appendix A [7,23,24]. Figure 1 and Supplemental Material Fig.…”
Section: A Mhz Synchrotron-x-ray Imaging Of Laser-induced Spatteringmentioning
confidence: 99%
“…Recent work has used synchrotron X‐ray imaging to probe how melt‐pool behavior relates to spatter and melt‐pool dynamics in conditions approximating overhang regions, which are particularly defect‐prone regions in bulk part builds . Cunningham et al imaged the melt pool and vapor depression on bare Ti64 using synchrotron‐based X‐rays to study how the power and velocity of the incident laser beam affected the heat‐transfer mode of the sample (i.e., conduction or keyhole mode) and its relation to laser drilling speed, vapor depression dynamics, and front keyhole wall angle . Herein, we utilize high‐speed X‐ray imaging to quantify subsurface‐defect formation and dynamics during the LPBF process in Ti64.…”
Section: Introductionmentioning
confidence: 99%
“…In some AM technologies which use high-density powers, material might be deposited or melted in keyhole mode, which is a melt pool with a deep and narrow shape. Cunningham et al [8] showed the threshold, morphology, and different stages of keyhole formation through X-ray imaging, and suggested that different combinations of laser power density and scanning velocity might result in the formation of keyholes; 2.…”
Section: Introductionmentioning
confidence: 99%